P3.055 Herpes Simplex Type 2 (HSV-2) Incidence by Age and Sex Over Four Age Periods to Age 38 Years in a Birth Cohort. (13th July 2013) - Dickson, N; Righarts, A; Roode, T van; Paul, C; Taylor, J; Cunningham, T
Abstract : Background: Here we report direct measures of HSV-2 incidence over four age periods to age 38 in the Dunedin Multidisciplinary Health and Development Study, a long-running New Zealand birth cohort. Methods: Information on sexual behaviour and STIs was obtained at ages 21, 26, 32 and 38. Sera were collected at these ages and tested for HSV-2 antibodies using an indirect enzyme-linked immunosorbent assay. Incidence rates for four age periods (< 21, 21–26, 26–32 and 32–38) were calculated and compared by age and sex. Results: The seroprevalence of HSV-2 antibodies at age 38 was 14.0% (63/451) for men and 23.7% (107/451) for women (p = 0.001). The number becoming HSV-2 positive in each age period, and the associated incidence rate per 1000 person-years (95% CIs), are shown below. The peak period of HSV-2 risk (after adjustment for number of sexual partners) was 21–26 for women, and 26–32 for men. It was significantly higher for women in the period 21–26. Conclusion: In this birth cohort HSV-2 is common, more so in women. The elevated risk for people in their twenties, that peaks later among men, is likely due to increasing prevalence among their partners. However, this did not result in continued increasing incidence into their thirties as would be expected. The most plausible explanation for the drop in incidence is that individuals' infectivity is decreasing with time, so that while prevalence among partners continues to rise, those with HSV-2 will on average have been infected for longer and be less infectious.